Single‐center experience of ex vivo lung perfusion and subsequent lung transplantation. Issue 2 (11th January 2023) - Noda, Kentaro; Chan, Ernest G.; Furukawa, Masashi; Ryan, John P.; Clifford, Sarah; Luketich, James D.; Sanchez, Pablo G.
Abstract: Background: The safety of lung transplantation using ex vivo lung perfusion (EVLP) has been confirmed in multiple clinical studies; however, limited evidence is currently available regarding the potential effects of EVLP on posttransplant graft complications and survival with mid‐ to long‐term follow‐up. In this study, we reviewed our institutional data to better understand the impact of EVLP. Methods: Lungs placed on EVLP from 2014 through 2020 and transplant outcomes were retrospectively analyzed. Data were compared between lungs transplanted and declined after EVLP, between patients with severe primary graft dysfunction (PGD3) and no PGD3 after EVLP, and between matched patients with lungs transplanted with and without EVLP. Results: In total, 98 EVLP cases were performed. Changes in metabolic indicators during EVLP were correlated with graft quality and transplantability, but not changes in physiological parameters. Among 58 transplanted lungs after EVLP, PGD3 at 72 h occurred in 36.9% and was associated with preservation time, mechanical support prior to transplant, and intraoperative transfusion volume. Compared with patients without EVLP, patients who received lungs screened with EVLP had a higher incidence of PGD3 and longer ICU and hospital stays. Lung grafts placed on EVLP exhibited a significantly higher chance of developing airway anastomotic ischemic injury by 30 days posttransplant. Acute and chronic graft rejection, pulmonary function, and posttransplant survival were not different between patients with lungs screened on EVLP versus lungs with no EVLP. Conclusion: EVLP use is associated with an increase of early posttransplant adverse events, but graft functional outcomes and patient survival are preserved.